2013
DOI: 10.5812/jjm.10088
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Mycoplasma hominis and Ureaplasma urealyticum in Females With Urogenital Infections and Habitual Abortion History in Ahvaz, Iran; Using Multiplex PCR

Abstract: Background: Infections due to Mycoplasmatales members can cause infertility, preterm delivery and neonatal morbidity and mortality. Therefore, rapid diagnosis is of great importance to control these infections and diminish their outcomes. Objectives: The current study aimed to develop the multiplex PCR assay to detect two genital mollicutes from a single amplification reaction and the study of their relation with habitual abortion and urogenital infection in infected females. Materials and Methods: Urine and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…In the present study, in patients with primary infertility ( Table 3 ), analysis revealed that the highest prevalence of Mollicutes infection was that of M. hominis (12.6%) followed by U. urealyticum (6.8%) and M. genitalium (4.9%), whereas U. urealyticum (3.9%) possessed the highest prevalence of Mollicutes among patients with secondary infertility followed by M. genitalium and M. hominis (2.9%). This finding was in agreement with the previous report on recurrent (habitual) abortion in the presence of theses Mollicutes [ 23 ]. Bayoumi et al [ 24 ] also reported that M. hominis was detected in 30.4% of women with repeated pregnancy loss and not in pregnant women (as control) and the presence of M. hominis was observed more frequently in women with repeated abortions.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, in patients with primary infertility ( Table 3 ), analysis revealed that the highest prevalence of Mollicutes infection was that of M. hominis (12.6%) followed by U. urealyticum (6.8%) and M. genitalium (4.9%), whereas U. urealyticum (3.9%) possessed the highest prevalence of Mollicutes among patients with secondary infertility followed by M. genitalium and M. hominis (2.9%). This finding was in agreement with the previous report on recurrent (habitual) abortion in the presence of theses Mollicutes [ 23 ]. Bayoumi et al [ 24 ] also reported that M. hominis was detected in 30.4% of women with repeated pregnancy loss and not in pregnant women (as control) and the presence of M. hominis was observed more frequently in women with repeated abortions.…”
Section: Resultssupporting
confidence: 94%
“…It was also recorded that genital colonization with M. hominis and U. urealyticum may predispose to spontaneous abortion [ 22 ]. A previous study by Maleki et al [ 23 ] revealed a direct strong relationship between M. hominis and U. urealyticum and habitual abortion as well as urogenital infections. Furthermore, the role of Mollicutes in causing miscarriage is supported by treatment results of 5 female patients who had suffered from miscarriage and were included in our research.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Peerayeh et al (2007) (27) reported that of the 377 patients studied, 141 samples (37.4%) were positive for U. urealyticum , which was higher than our results. A previous study from Ahvaz, Iran ( 28 ) showed that the prevalence of M. hominis and U. urealyticum in the genital samples of females were 6.4% and 13.6%, respectively. They showed that the highest prevalence of M. hominis (54.5%) and U. urealyticum (53.8%) was found in females within 28 - 33 and 34 - 39 years old.…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of UU has been reported to be 20% in South America, 41.9% in Italy, and 51.5% in Africa [ 14 ]. The highest prevalence of UU (53.8%) was detected in females between 34 and 39 years of age [ 15 ].…”
Section: Discussionmentioning
confidence: 99%